2023
DOI: 10.1111/jgs.18283
|View full text |Cite
|
Sign up to set email alerts
|

Association of early acute‐phase rehabilitation initiation on outcomes among patients aged ≥90 years with acute heart failure

Abstract: Background Data on the potential benefit of acute‐phase rehabilitation initiation in very old (aged ≥90) patients with acute heart failure (AHF) have been scarce. Methods We retrospectively analyzed data from the Diagnosis Procedure Combination database, which is a nationwide inpatient database. This study included patients hospitalized for heart failure (HF) from January 2010 to March 2018, those aged ≥90 years, who had a length of stay of ≥3 days, New York Heart Association (NYHA) class of ≥II, and had not u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Furthermore, among 25,000 patients admitted to the ICU for AHF, the implementation of acute CR led to decreased in-hospital mortality and reduced hospitalization duration [59] . Therefore, based on prior research findings and the outcomes of our study, we can infer that initiating rehabilitation early in patients with AHF is advantageous [47–49,57–58] .…”
Section: Big Data Analysis Reveals the Importance Of Physical Activitymentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, among 25,000 patients admitted to the ICU for AHF, the implementation of acute CR led to decreased in-hospital mortality and reduced hospitalization duration [59] . Therefore, based on prior research findings and the outcomes of our study, we can infer that initiating rehabilitation early in patients with AHF is advantageous [47–49,57–58] .…”
Section: Big Data Analysis Reveals the Importance Of Physical Activitymentioning
confidence: 83%
“…2023 [46] People with unhealthy behavior separately; smoking habits (n = 365,259), physical inactivity (n = 759,272), skipping breakfast The research underscores the importance of exercise habits in this lifestyle change, indicating that cultivating regular exercise habits can play a crucial role in preventing CVD Acute-phase initiation of cardiac rehabilitation for short-term improvement in activities of daily living in patients hospitalized for acute heart failure [47] J Cardiovasc Dev Dis. 2022 [47] 306,826 patients hospitalized for HF Improvement in ADL Acute-phase CR initiation may result in short-term improvement in ADL in patients hospitalized for acute HF Association of early acutephase rehabilitation initiation on outcomes among patients aged ≥90 years with acute heart failure [48] J Am Geriatr Soc.…”
Section: Cr For Patients With Acute Hf (Ahf)mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that initiation of acute-phase CR improved short-term clinical outcomes including length of stay, 30-day readmission rate due to HF, and all-cause 30-day readmission in patients aged ≥90 years with AHF. 9 Additionally, initiation of outpatient CR after discharge reduced deaths and readmissions for HF without increasing medical costs. 10 However, in the FLAGSHIP study, outpatient CR after discharge of older adults with HF improved the short-term but not the long-term prognosis.…”
Section: Clinical Practice For Acute Heart Failure In Japanmentioning
confidence: 99%